Epistimologi Ilmu Pengetahuan dalam Perspektif John Locke dan Al-ghazali - Fadhli Hafizh; Rohanda Rohanda; Abdul Kodir (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: This article discusses the epistemology of knowledge from the perspectives of John Locke and Al-Ghazali. It also examines three Western epistemological schools: rationalism, empiricism, and criticism, as well as three Islamic intellectual traditions: bayani, burhani, and irfani. The study conducts a comparative analysis of the epistemologies of Al-Ghazali and John Locke, aiming to provide a comprehensive overview of their thoughts and examine the epistemological implications for the dynamics of knowledge and religion.John Locke developed the empiricist school, emphasizing the importance of experience in acquiring knowledge. He criticized the rationalist view that relies solely on reason while still acknowledging reason's role in understanding the world. In contrast, according to Al-Ghazali, true epistemological understanding comes from knowledge directly granted by God, inherent within an individual, signifying a person's spiritual closeness to God.Keywords: Al-Ghazali, Epistimology, John Lock. Abstrak: Artikel ini membahas epistemologi ilmu pengetahuan dalam perspektif John Locke dan Al-Ghazali. John Locke, Artikel ini juga mengkaji tiga aliran epistemologi Barat: rasionalisme, empirisme, dan kritisisme, serta tiga tradisi pemikiran Islam: bayani, burhani, dan irfani. Penelitian ini melakukan kajian komparatif terhadap epistemologi al-Ghazali dan John Locke dengan tujuan untuk memberikan gambaran yang komprehensif mengenai pemikiran keduanya, serta mengkaji konsekuensi epistemologis mereka terhadap dinamika ilmu pengetahuan dan agama.jonh Locke mengembangkan aliran empirisme yang menekankan pentingnya pengalaman dalam memperoleh pengetahuan. Ia mengkritik pandangan rasionalis yang terlalu mengandalkan akal semata, namun tetap mengakui peran akal dalam memahami dunia. Sedangkan Menurut Al-Ghazali, pemahaman epistimologi ilmu yang benar adalah hasil dari pengetahuan yang berasal langsung dari Allah dan telah melekat dalam diri seseorang. Hal ini menandakan kedekatan spiritual seseorang dengan Tuhan.Kata kunci: Epistimologi , John Locke , Al-Ghazali.